2019
DOI: 10.24252/alami.v3i2.9795
|View full text |Cite
|
Sign up to set email alerts
|

Tingkat Pengetahuan Dan Kebiasaan Sarapan Mahasiswa Program Studi Pendidikan Dokter Uin Alauddin Makassar Tahun 2017

Abstract: AbstrakSarapan adalah kegiatan makan dan minum yang dilakukan antara bangun pagi sampai jam 9 pagi. Sarapan memiliki peranan yang sangat penting baik bagi kesehatan maupun konsentrasi belajar. Masyarakat Indonesia belum terbiasa dengan sarapan. Program Studi Pendidikan Dokter Fakultas Kedokteran dan Ilmu Kesehatan UIN Alauddin Makassar (PSPD FKIK UINAM) menganut metode pembelajaran dengan menitikberatkan pada Student Centred Learning (SCL) dimana mahasiswa dituntut untuk proaktif , dan perkuliahan dimulai dari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…A study revealed that there was no significant relationship between gender and the frequency of students' breakfast. 11 The results of other studies also stated that gender had no relationship with the breakfast habit of the respondents. Since the breakfast behavior of male and female subjects is similar, many subjects choose breakfast at home rather than having snacks during the day, and the habit of both subject groups showed no significant difference.…”
Section: Discussionmentioning
confidence: 90%
“…A study revealed that there was no significant relationship between gender and the frequency of students' breakfast. 11 The results of other studies also stated that gender had no relationship with the breakfast habit of the respondents. Since the breakfast behavior of male and female subjects is similar, many subjects choose breakfast at home rather than having snacks during the day, and the habit of both subject groups showed no significant difference.…”
Section: Discussionmentioning
confidence: 90%